Evaluation of nutritional status and eating behavior in Romanian pediatric population - Simona Loredana Vasilache; Anastasia Boaghi; Raluca-Monica Pop; Claudia Banescu; Valeriu Moldovan; Carmen Duicu; Ionela Maria Pascanu; Oana Marginean (Amaltea Medical Publishing House, 2020)
Objectives. Numerous factors have been associated with hight prevalence of obesity, nutrition being the most important factor. The aim of this study was to evaluate the eating behavior of school children in Targu Mures and to evaluate the impact on auxological parameters. Material and method. The study included 213 children divided in 2 groups (107 females, 106 males), aged 5-18, evaluated in the Pediatrics I and Endocrinology Clinic in Târgu Mureș. The evaluation included: auxological data, body composition using bioimpedance. Participants reported eating behavior using a 126-item food frequency questionnaire. The results were classified as concentrated sweets, fats, meat, fruits and vegetables, cereals and dairy products. Results. There are no statistically significant differences between the 2 groups regarding the food pyramid. However, in boys, there are statistically significant correlations between fat consumption and weight (r = 0.198, p = 0.042) and body water (r = 0.209, p = 0.044), and the consumption of meat correlates with weight (r = 0.249, p = 0.010), abdominal circumference (r = 0.258, p = 0.008) and waist-height ratio (r = 0.193, p = 0.048). In girls, there is no singnificant correlations between intake of studied food group and anthropometric parameters. Conclusions. The results highlight the importance of eating behavior, which has a major impact in obesity prevalence. In our study, there are correlations between concentrated fats and meat consumption and adiposity markers in boys. Prospective studies are needed to identify how different types of food related to body composition and central obesity in pediatric population.